Cajamarca: Mapping (Post)Mining Palimpsests of the Peruvian Andes - Macera, Margarita (2020)
Mining, in addition to other human activities and natural phenomena, has repeatedly reshaped the landscapes of the Peruvian Andes. Long-standing, significantly modified and new Andean landscapes have resulted in a complex reading of the ‘land as palimpsest’ (Corboz, 1983). In recent decades, large-scale modern mining has disturbed headwater landscapes and broader Andean ecologies, as exemplified in Cajamarca’s gold mines. This article critically reads past and present spatial transformations induced by gold mining in the headwaters of the Cajamarca Basin. Through archival documentation, fieldwork and interpretative cartography, it analyses the large-scale surface mining operations in Cajamarca from 1993 to 2020, as well as their impact on downstream rural and urban ecologies. A cross-scalar mapping investigation discloses the spatial-ecological outcomes of twenty-seven years of mining (and closure) operational procedures. As a conclusion of the palimpsest reading, a design-research question is posed as to how Cajamarca’s post-mining landscapes can be opportunely premeditated. It hypothesizes that, already during exploitation, the post-mining landscapes can be consciously constructed by an intelligent manipulation of mining procedures and create a layer of the territory that is more robust. Environmental reconstruction after mining closure recreates a pseudo-natural environment that supposedly erases the traces of mining and restores natural condition—literally back to nature, with no cultural trace. In this regard, reconstruction is merely theoretical since the repairing to a natural state would mean no palimpsests. However, despite the most imaginative and ecological repair, the territory remains a mega palimpsest, cruelly violated and disrupted. Therefore, at best, the proposition can be to build a cultural, consciously conceived and tailored post-mining landscape, merging mining and post-mining landscape construction into one movement, where the remaining (palimpsest) is part-and-parcel of the newly constructed.